Funds Based On Sharia Free - Ayu Safrianti; Irmawati Irmawati; Nitia Mantasya; Dewi Rahmadhani (Proceeding International Seminar of Islamic Studies, 2019)
Working capital is a very important element for a company because without sufficient working capital, the companys operational activities cannot be carried out. With the rapid development of the business world at this time resulting in intense competition among similar companies, obtaining capital adequacy is a major factor that needs attention. To be able to compete with other companies, a company must be able to manage all its wealth, crafts and capital as much as possible so that the companys operational activities can run well. Analysis and use of working capital, liquidity ratios, current ratio, are often used as indicators to assess the effectiveness and efficiency of a companys working capital and measure its ability to pay off all its short-term obligations